Dynamics of Economic Factors Influencing Human Development in ASEAN-7 - Kurniawan, Bagja (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2022)
Abstract This study analyzes the relationship between economic factors and human development in the seven ASEAN countries using the panel data regression approach and Moderated Regression Analysis (MRA). The factors investigated include international trade (TRD), per capita GDP growth (GrGDPPC), inflation (INF), and economic freedom (EFI). Panel data covers seven ASEAN countries during the 2012–2020 time period. Based on the results of the panel data regression analysis, it was found that only the inflation variable did not have a significant effect on human development. Meanwhile, the results of the MRA analysis show that economic freedom acts as a quasi-moderation in the relationship between international trade and human development. Meanwhile, economic freedom also functions as an independent variable in influencing the growth of GDP per capita and inflation in human development. These findings provide a deeper understanding of the complexity of the interactions between economic factors shaping HDI achievement in ASEAN. Keywords: ASEAN, economic freedom, human development JEL: O15, F43, E31, I32